Lesson Study: A Tool for an Improved Instructional Design in Teaching Integration by Parts - et.al, Daisy Lyn F. Mariano (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to develop instructional design in teaching the Integration by Parts in Calculus. By engaging in a Lesson Study, the researchers underwent careful planning of the design, executed it through a research lesson, noted key observations during the delivery of the lesson, and conducted a post-lesson conference. From the observations and insights during the post-conference, two themes emerged from where recommendations were drawn. The first theme pivoted on the propensity of teaching Integration by Parts as highly procedural and mechanical despite attempts at activating students’ higher-order thinking. However, the extent to which the tabular method could be advantageous should be explained to the students to clarify misconceptions about using it as a shortcut in performing Integration by Parts. The second theme revolved around how supportive classroom environment and the use of Tabular Method made the students more engaged. Nevertheless, providing learning experiences where students can be work on higher-order thinking and where they can process results of their collaboration was recommended to be incorporated in the instructional design. Generally, both Tabular and Conventional Methods play a crucial role in developing students’ mastery of this integration technique and may eventually allow them to make connections to the real world